Love to everyone - McKay, Hilary (Margaret K. McElderry Books, 2018)
In 1902 England, Clarry and Peter struggle with the challenges of living with an indifferent father, but the summers they spend in Cornwall with their grandparents and cousin Rupert provide much needed comfort, and in the years that follow Clarry looks back on those leisurely days to help her cope with the trying times of World War I and its aftermath.